2015
DOI: 10.1051/0004-6361/201526903
|View full text |Cite
|
Sign up to set email alerts
|

HARPS spectropolarimetry of three sharp-lined Herbig Ae stars: New insights

Abstract: Aims. Recently, several arguments have been presented that favour a scenario in which the low detection rate of magnetic fields in Herbig Ae stars can be explained by the weakness of these fields and rather large measurement uncertainties. Spectropolarimetric studies involving sharp-lined Herbig Ae stars appear to be a promising approach for the detection of such weak magnetic fields. These studies offer a clear spectrum interpretation with respect to the effects of blending, local velocity fields, and chemica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…the presence of small shifts in the LSD Stokes V profiles obtained for the neutral Fe and Ti ii lists indicates that we probably observe a contamination by the surrounding warm circumstellar (CS) matter in the form of a wind. Such a scenario was already discussed by Järvinen et al (2015) and would be in agreement with the previous finding of Hubrig et al (2009) who reported a strong contamination of the UVES spectra of this star by weak lines of neutral and ionized iron (see their Fig. 6), where the lines of neutral iron are by far more numerous than those of ionized iron.…”
Section: Magnetic Field Measurementssupporting
confidence: 92%
See 4 more Smart Citations
“…the presence of small shifts in the LSD Stokes V profiles obtained for the neutral Fe and Ti ii lists indicates that we probably observe a contamination by the surrounding warm circumstellar (CS) matter in the form of a wind. Such a scenario was already discussed by Järvinen et al (2015) and would be in agreement with the previous finding of Hubrig et al (2009) who reported a strong contamination of the UVES spectra of this star by weak lines of neutral and ionized iron (see their Fig. 6), where the lines of neutral iron are by far more numerous than those of ionized iron.…”
Section: Magnetic Field Measurementssupporting
confidence: 92%
“…The absence of δ Scuti-like pulsations was already discussed in the previous work of Järvinen et al (2015) where the authors verified that no changes in the line profile shape or radial velocity shifts are present in the obtained spectra on a short-time scale. This step was of importance since pulsations are known to have an impact on the analysis of the presence of a magnetic field and its strength (e.g.…”
Section: Spectral Variabilitysupporting
confidence: 69%
See 3 more Smart Citations